The Price Responsiveness of Housing Supply in OECD Countries - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2011)
The responsiveness of housing supply to changes in prices bears important implications for the evolution of housing prices and the speed of adjustment of housing markets. This paper estimates the long-run price elasticity of new housing supply in 21 OECD countries based on a stock-flow model of the housing market estimated within an error correction framework. Estimates suggest that housing supply responsiveness to price changes varies substantially across countries. New housing supply is relatively more flexible in North America and some Nordic countries, while it is more rigid in continental European countries and in the United Kingdom. The responsiveness of housing supply depends not only on national geographical and urban characteristics but also on policies, such as land use and planning regulations. The estimates are broadly in line with the limited available evidence on the responsiveness of housing supply in OECD countries